O professor da sala de recursos multifuncionais e o uso das tecnologias assistivas - Reis, Anderson de Araujo (2021)
The possibilities of the teacher's performance in the Multifunctional Resources Room are numerous, as their activities differ due to the most diverse types of disability and impairment. Thus, it is essential to the inclusion process that the teacher is in a continuous training process. This research aimed to understand how teachers appropriate Assistive Technologies in the Multifunctional Resource Room. And it is anchored in the assumptions of inclusive education and Assistive Technologies, having as a link the appropriation of teachers. The concept of appropriation of ATs is endorsed by Galvão Filho (2012) as the possible fundamental processes for the identification of needs, acquisition, training and proper use. It was chosen as the object of study the teachers who work in the Multifunctional Resource Room of schools under the jurisdiction of the Board of Education of Aracaju/SE. The research has a qualitative nature and for the method of data analysis, we chose Content Analysis from the perspective of Bardin's (2011) categorization under the lens of Amado (2017) and Crusoé (2014). Data collection was carried out in two phases, the first with the application of a questionnaire with the intention of identifying which teachers met the research criteria and the second phase with a comprehensive interview with six teachers, in order to obtain procedures systematically from the descriptions content of the messages that allowed the structuring of thematic axes. The survey data revealed that the process of appropriation as accessibility resources is allied to several existing barriers, with contradictions and disconnections permeated in the context which make it impossible for the teacher to proceed on the path of constant learning and deepening using the arsenal of Assistive Technologies resources that directly contribute to the process of permanence, participation and learning of students with disabilities at school.